Mental wellbeing during pregnancy and the transition to motherhood: an explorative study through the lens of healthcare professionals - Katarina Ekelöf; Gerd Almquist Tangen; Christine Delisle Nyström; Marie Löf; Kristin Thomas (BMC Pregnancy and Childbirth)
Abstract Background The perinatal period can be an overwhelming time involving significant physiological and psychosocial changes. The perinatal period has shown to be a time of increased vulnerability for onset or relapse of mental health problems (e.g., depression, anxiety). Mental wellbeing such as resilience have positive effects on women’s physical and mental health during pregnancy as well as on pregnancy related outcomes. However, more knowledge is needed on perinatal mental wellbeing and how it can be promoted. This qualitative study explores mental wellbeing during the perinatal period and promoting factors through the lens of healthcare professionals. Methods Individual interviews were conducted with healthcare professionals (n = 16) through the chain of care from pregnancy to post-partum (i.e., maternity healthcare, maternity wards and child healthcare) and included midwives, obstetricians, psychologists and child healthcare nurses. A semi-structured interview guide and open-ended questions were used, and inductive content analysis was performed. Results In analysis, an overarching theme: “The being and the becoming of a mother – equanimity in the transition to motherhood” emerged to describe mental wellbeing during the perinatal period. Three main categories were found to describe factors promoting mental wellbeing: (i) Inner resources (e.g., trusting the process of pregnancy), (ii) Experiencing trust during the transition (e.g., having someone to share experiences with), and (iii) Having access to a caring and supportive network (e.g., emotional support). These factors were described by professionals as being important for mental wellbeing as they help women during their transition to motherhood. Conclusion Mental wellbeing during the transition to motherhood can be promoted by supporting and building resources for equanimity. Findings emphasize the need to target mental health promoting factors on multiple levels including strengthening the inner resources of the individual but also building social support structures around the individual.